Association between dietary niacin intake and atherosclerotic cardiovascular disease among American adults: national health and nutrition examination survey - Li, Yan; Yang, Beilei; Li, Na; Wei, Jinjuan; Wu, Yue (Frontiers in Nutrition, 2025)
BackgroundThe relationship between dietary niacin and atherosclerotic cardiovascular disease (ASCVD) is still not fully understood. Our objective was to assess the association between dietary niacin intake and the prevalence of ASCVD.MethodsIn this cross-sectional study, we examined a cohort of 15,685 adult individuals in the United States, aged 20 years and older, who participated in the National Health and Nutrition Examination Survey (NHANES) carried out between 2007 and 2014. Dietary Niacin consumption was assessed using a 24-h dietary recall method. The assessment of the presence of ASCVD was conducted through the Patient Medical Conditions Questionnaire. To assess the reliability of the results, restricted cubic spline models and logistic regression analyses were employed, along with conducting subgroup analyses.ResultsThe analysis included 15,685 participants who were 20 years or older, drawn from the NHANES data for the cycles spanning 2007 to 2014. Of which 10.4% (1,638/15,685) were diagnosed with ASCVD. The probability of ASCVD diminishes by 9% with each 10 mg/day increment in dietary niacin intake (OR = 0.91, 95% CI: 0.87–0.96). This association held true when niacin consumption was assessed as a categorical variable. Compared to individuals with the lowest dietary niacin intake, defined as T1 (≤17.4 mg/day), the adjusted odds ratios for ASCVD in those with higher niacin intakes, T2 (17.5–27.2 mg/day) and T3 (≥27.3 mg/day), were 0.87 (95% CI: 0.76–0.99, p = 0.037) and 0.75 (95% CI: 0.64–0.87, p < 0.001), respectively. There was an inverse association between dietary niacin intake and ASCVD prevalence, supported by sensitivity analyses. Subgroup analysis revealed an interaction effect when stratified by age.ConclusionThis analysis of NHANES data has demonstrated that niacin is significantly negative associated with ASCVD in American adults aged ≥20 years.